The depletion of gut microbiome impairs the beneficial effect of Gui-Shen-Wan in restoring mice ovarian function and associated protein expression of ovarian tissues - Huang, Xingtao; Xu, Ruinan; Yang, Qin; Jiang, Xin; Lin, Jinju; Zhao, Huashan; Wu, Ruifang; Du, Hui; Dai, Wenkui (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionTraditional Chinese Medicine (TCM), specifically Gui-Shen-Wan, has shown promise in restoring ovarian function among reproductive-age women who had impaired ovarian functions, yet the underlying mechanisms remain elusive. Recent studies highlight the pivotal role of the gut microbiome (GM) in mediating the therapeutic effects of TCM. However, it is unclear whether the GM contributes to Gui-Shen-Wan’s therapeutic restoration of ovarian functions.MethodsThis study employed a mouse model with cyclophosphamide-induced decreased ovarian function (P_T and P_AT groups) and a control group without modeling. The P_AT group received a 7-day course of oral antibiotics to deplete the GM prior to a 20-day Gui-Shen-Wan treatment regimen.ResultsBoth P_T and P_AT mice exhibited prolonged metestrus/diestrus phases compared to controls (p<0.05), indicating menstrual disruption post-modeling. Following 20 days of Gui-Shen-Wan treatment, P_T mice showed a shorter metestrus/diestrus phase (4 days) compared to P_AT mice (5 days) (p<0.05). Notably, P_T mice had a higher number of normal follicles(primitive/primary/secondary/antral follicles) in their ovaries post-treatment (median 15) compared to P_AT mice (median 8.5). Proteome analysis revealed that ovarian proteins enriched in P_T mice were primarily associated with oxidative phosphorylation and DNA replication pathways, suggesting GM-mediated enhancement of these processes.DiscussionThis study underscores the pivotal role of the GM in the therapeutic benefits of Gui-Shen-Wan, highlighting the potential for microbiome-targeted interventions in promoting beneficial effects of Gui-Shen-Wan on the restoration of decreased ovarian functions.